Real-world evidence of nivolumab for non-small-cell lung cancer in a developing country. (June 2023) - Luján, Mauricio; Lema, Mauricio; Preciado, Beatriz; Lema, Camila; Egurrola, Jorge; Cardona, Andrés; González, Diego; Mantilla, William; Pino, Luis; Rojas, Gustavo; Gómez, Diego; Munevar, Isabel; et al.
Nivolumab is a human programmed death receptor-1 blocking antibody, used as treatment option in patients with advanced non-small-cell lung cancer (NSCLC). We assessed the nivolumab efficacy in terms of survival and response to treatment as second-line (2L) or third-line (3L) therapy in patients with advanced NSCLC. This is a multicentric observational study. Data of patients with advanced NSCLC who received nivolumab as 2L or 3L treatment were analyzed retrospectively. Information regarding patient demographics and clinical backgrounds, treatment patterns from diagnosis to post-nivolumab treatment, effectiveness, and safety of nivolumab treatment were collected. The outcomes evaluated were overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) to treatment. OS and PFS were estimated with the Kaplan–Meier method and the differences were evaluated through the log-rank test. Data of 178 patients were included. The median follow-up was 26.8 months (interquartile range (IQR): 20.3–40.4). Nivolumab was commonly used as a 2L treatment (77.5%). The outcomes in this setting (2L) were as follows: ORR was 21.0%, and the median PFS and OS were 5.5 months (95% confidence interval (CI): 4.5–6.5) and 12.4 months (95% CI: 10.8–14.0), respectively. In 3L, the ORR with nivolumab was 15.0%, the median PFS and OS were 4.1 months (95% CI: 3.1–5.1) and 10.1 months (95% CI: 9.4–10.6), respectively. Three patients (1.7%) required discontinuation due to toxicity. Nivolumab effectiveness and safety in this scenario was consistent with that reported by previous trials and other real-world data.